Karl Barth"s male-female order as asymmetrical theoethics - Dreyer, Yolanda (HTS teologiese studies, 2007)
This article is to argues that Karl Barth’s revelation-based theology represents male bias entrapped within patriarchal Christian tradition. The rigid way of using the revelation-based model in exegesis and theology goes against the grain of Barth’s otherwise flexible epistemology. It is particularly evident in the connection between Barth’s theoetics and his view on the subordination of women. In two articles written from a gender critical perspective the focus of the first article is on Barth’s asymmetrical theoethics and that of the second on the disparity in his dogmatics. The aim of the first article is to trace the influence of the Christian tradition (including early Christianity) on his theology. The aim of the second article is to explain Barth’s dogmatic disparity as the product of his neoorthodox understanding of Reformed tradition.